Oncogenes and Tumor Suppressors Regulate Glutamine Metabolism in Cancer Cells - Kim, Min Hyun (Korean Society of Cancer Prevention, 2013)
Several hallmarks of cancer cells are their display of metabolic changes and enhanced proliferation. Highly proliferating cells utilize glutamine as a source of nitrogen, and therefore, one of the commonly seen metabolic changes is increased glutaminolysis, or glutamine catabolism. In addition, glutamine is an important anaplerotic source by which cells support the pools of TCA cycle intermediates in Myc-expressing cancer cells. Glutamine is converted to aspartate, which forms oxaloacetate, malate, and pyruvate. These conversions increase the NADPH/NADP(+) ratio and maintain redox balance, which supports proliferation in K-ras-expressing cells. Therefore, glutamine is important for cancer cell proliferation and survival. On the other hand, glutamine stimulates the activation of the tumor suppressor p53, which induces apoptosis and tumor regression. The tumor suppressor SIRT4 inhibits glutamate dehydrogenase, which converts glutamic acid to α-ketoglutarate, an intermediate in the TCA cycle. Overall, the expression levels of oncogenes and tumor suppressors are critical to determine whether glutamine supports or suppresses proliferation and survival of cancer cells.